5 Implementation of a sensitive troponin I assay reduces death and recurrent myocardial infarction in patients with suspected acute coronary syndrome. (9th June 2011) - Lee, K K; Mills, N L; Churchhouse, A M D; Anand, A; Gamble, D; Shah, A; Paterson, E; MacLeod, M; Graham, C; Walker, S; Denvir, M A; Fox, K A A; et al.
Abstract : Introduction: Although troponin assays have become increasingly more sensitive, it is unclear whether further reductions in the threshold of detection for plasma troponin concentrations impact on clinical outcomes in patients with suspected acute coronary syndrome. The aim of this study was to determine whether lowering the diagnostic threshold for myocardial infarction with a sensitive troponin assay will improve clinical outcomes. Methods: Consecutive patients admitted with suspected acute coronary syndrome before (n=1038; validation phase) and after (n=1054; implementation phase) lowering the threshold of detection for myocardial necrosis from 0.20 to 0.05 ng/ml with a sensitive troponin I assay were stratified into three groups: <0.05, 0.05–0.19 and ≥0.20 ng/ml. During the validation phase, only concentrations above the original diagnostic threshold of ≥0.20 ng/ml were reported to clinicians. Event-free survival (reinfarction and death) at 1 year were compared in patients grouped by plasma troponin concentrations. Results: Plasma troponin concentrations were <0.05 ng/ml in 1340 (64%), 0.05–0.19 ng/ml in 170 (8%) and ≥0.20 ng/ml in 582 (28%) patients. During the validation phase, 39% of patients with undisclosed plasma troponin concentrations of 0.05–0.19 ng/ml were dead or had recurrent myocardial infarction at 1 year, compared to 7% and 24% of those with troponin concentrations <0.05 ng/ml (p<0.001) or ≥0.20 ng/ml (p=0.007) respectively. During the implementation phase, lowering the diagnostic threshold to 0.05 ng/ml reduced 1-year death and recurrent myocardial infarction from 39% to 21% in patients with troponin concentrations of 0.05–0.19 ng/ml (OR 0.42, 95%CI 0.24 to 0.84, p=0.013), whereas clinical outcomes were unchanged in patients with troponin concentrations <0.05 ng/ml or ≥0.20 ng/ml (Abstract 5 figure 1 ). Conclusions: In patients with suspected acute coronary syndrome, implementation of a sensitive troponin assay increases the diagnosis of myocardial infarction by a third, and identifies those at high-risk of reinfarction and death. Lowering the diagnostic threshold of plasma troponin is associated with major reductions in morbidity and mortality.